2015
DOI: 10.1002/2015jd023589
|View full text |Cite
|
Sign up to set email alerts
|

Dust aerosol feedback on the Indian summer monsoon: Sensitivity to absorption property

Abstract: We examine the sensitivity of dust radiative feedback to the dust absorption property during the Indian summer monsoon (June–September) season from 2005 to 2010 using the Regional Climate Model version 4.1. The dust direct radiative forcing at top of atmosphere switches from cooling to warming for absorbing dust over the Indian subcontinent. The dust‐induced low pressure anomaly plays a crucial role in building up large‐scale convergence particularly over the Arabian Peninsula, which strengthens the monsoon ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 54 publications
5
32
0
1
Order By: Relevance
“…This result indicates that aerosols mostly consist of dust, smoke, and polluted dust during the monsoon season in South Asia, hence attaining consistency with previous work [44]. These aerosols present distinct absorbing effects on solar radiation, thereby attenuating the incoming solar radiation more intensively than other types of aerosols [45].…”
Section: Changes In Aerosolssupporting
confidence: 77%
See 1 more Smart Citation
“…This result indicates that aerosols mostly consist of dust, smoke, and polluted dust during the monsoon season in South Asia, hence attaining consistency with previous work [44]. These aerosols present distinct absorbing effects on solar radiation, thereby attenuating the incoming solar radiation more intensively than other types of aerosols [45].…”
Section: Changes In Aerosolssupporting
confidence: 77%
“…In addition, the resultant of the impacts of 3D aerosol, cloud, and water vapor are considerably complicated and varied given the intensive atmospheric activities during the monsoon season, and hence, this observation possibly contributes to the fluctuation of SSR variations during the monsoon season. The pre-monsoon season is the transition period from the dry to the monsoon seasons and is associated with establishing the southwestern wind regime over South Asia [44]. The atmospheric condition and radiation variations are indistinct compared with the trend of the SSR between the dry and monsoon seasons.…”
Section: Extended Discussion Of Seasonal Differencesmentioning
confidence: 99%
“…Changes in the wind regime between contrasting monsoon years associated with variations in the El-Nino Southern Oscillation (ENSO) seem to affect the dust outflow over the Arabian Sea (Abish and Mohanakumar, 2013). Larger dust-aerosol loading over the Arabian Sea is mostly related to normal rather than weak monsoon years (Rahul et al, 2008), while recent works (Vinoj et al, 2014;Solmon et al, 2015;Das et al, 2015) using satellite observations and model simulations found a positive feedback between Arabian dust outflow and rainfall over India.…”
Section: Introductionmentioning
confidence: 95%
“…Past studies have shown that the radiative roles of dust aerosol plays is largely dependent on SSA. A 5 % change in its value can significantly alter the magnitudes or even sign of SW radiative forcing (Hatzianastassiou et al, 2004;Solmon et al, 2008;Das et al, 2015b;Papadimas et al, 2012). Over the TP with SSA > 0.9, only less than 10 % of extinct solar radiation is absorbed by the dust aerosol, compared to 20-30% elsewhere, meaning that the TP dust aerosol is only onethird to one-half the efficiency of those over surrounding sources.…”
Section: Discussionmentioning
confidence: 99%
“…The semi-direct effects (Hansen et al, 1997) are included in this study as part of atmospheric feedback, but are not explicitly discussed here since they would be better discussed along with the indirect effects as both involve clouds. The simulated effects of dust aerosols on climate were highly sensitive to the physical characteristics of the dust aerosols, such as the SSA (Huang et al, 2014;Colarco et al, 2014;Das et al, 2015b). Therefore our results also need to be validated by sensitivity experiments using aerosols with different properties.…”
Section: Discussionmentioning
confidence: 99%